Penerapan Metode Fast Dalam Pengembangan Website Pemasaran Paket Wisata - Marini Marini (Universitas Asahan, 2022)
Marketing of tour packages needs to be developed to provide information about the beauty and attractiveness of the world of tourism in the territory of Indonesia. Tourism consists of objects and sights that are very stunning so as to provide positive beauty for tourism assets for the government, especially for foreign tourist visits. Indonesia is rich in very beautiful natural scenery. The income from this tourism asset is very large for the government and tourism promotion in Indonesia. It's a good idea, with the abundance of online information, which is still confusing, it is necessary to market regional tour packages. The purpose of applying the Fast Method in developing a Tour Package Marketing Website which is carried out online is to increase the level of consumer satisfaction in obtaining information, promising an increase in profits for the company. The method and model used is the Fast Method (Framework For Application Of System Thinking). The results to be achieved are to make it easier for the public to recognize access to tour package marketing, improve the quality of tourism, be fast in obtaining tourist information through the website that is applied